Kompetensi Keahlian, Pengalaman, Skeptisme Profesional Auditor, dan Situasi Audit terhadap Relevansi Pemberian Opini Audit atas Laporan Keuangan Entitas - Erllycha Novian Nur; Padlah Riyadi (Media Ilmiah Akuntansi, 2023)
This research is to examine and provide empirical evidence that the factor of expertise, experience, professional skepticism auditors and audit situation has no effect or no relevance to the provision of audit opinion on the financial statements of the entity. This research was conducted by using the sampling method is purposive sampling, with the type of quantitative research. Data was analyzed using multiple regression analysis models. Hypothesis testing is done to determine the extent of expertise, experience, professional skepticism auditors and audit situations affect the relevance of the provision of audit opinion on the financial statements entitatas either partially or simultaneously. Hypothesis testing results show that the experience and professional skepticism auditors partially or simultaneously positive effect on relevensi granting audit opinion on the financial statements of the entity, where as the expertise and audit situation does not affect the relevance of the provision of audit opinion on the financial statements of the entity.